The Impact of the Economic Crisis on the Dynamic of International Fdi - Lenuta Carp (CES Working Papers, 2012)
FDI flows are internationally recognized for the benefits they generate (technological transfer, know – how, industrial reorganization, raising the number of working places). Foreign capitals increased significantly under the impact of globalization and accelerated the interdependencies between economies up to 2007, but, in the current crisis, the dynamic of FDI flows was affected in a negative manner, both in developed economies and in the developing ones. The aim of this paper is to reveal and analyze the evolution of FDI flows in the period 2007 – 2010, emphasizing the strong impact that economic crisis exerts. The results of the analysis presents the descending trend up to 2009, since 2010 being noticed a slight recovery which continued in the first trimester of 2011 and according to the forecasts will continue in the future.
Keywords: E22; G01; G34; 330; FDI; crisis; economic growth; impact; mergers; acquisitions Romania